Prophylactic ondansetron for preventing intraoperative shivering, nausea and vomiting during spinal anesthesia for cesarean section: a randomized controlled trial - Zhang, Yuan; Xia, Fen; Zhang, Wangping; Lv, Anqing (Frontiers in Pharmacology, 2024)
Background: Shivering, nausea and vomiting are common complications in cesarean section during neuraxial anesthesia. The aim of this study was to investigate the effects of prophylactic use of ondansetron on intraoperative shivering, nausea and vomiting in women undergoing cesarean section.Methods: A total of 80 full-term parturients were randomly divided into the ondansetron group and the control group. The ondansetron group received 0.075 mg/kg of ondansetron 15 min before anesthesia, the control group were given the same volume of saline solution. The incidence of shivering, nausea and vomiting was noted. The occurrence and severity of shivering and other outcomes, such as hypotension, bradycardia and dizziness were recorded during the surgery. Umbilical arterial blood was analyzed, and the neonatal Apgar scores were assessed.The incidence of grade ≥1 shivering was lower in ondansetron group. The incidence of shivering, nausea and vomiting was significantly lower in ondansetron group than the control group (2.5% vs. 22.3%, P = 0.007, 2.5% vs. 40%, P = 0.001, respectively). No significant differences were observed in the incidence of hypotension, bradycardia, headache and dizziness between the 2 groups (P > 0.05). The umbilical artery pH and neonatal Apgar score were similar between the 2 groups (P > 0.05).Prophylactic use of ondansetron could prevent intra-operative shivering and reduce the incidence of nausea and vomiting in cesarean section under spinal anesthesia without increasing the incidence of maternal and infant adverse events.(Registration number: ChiCTR2100042453).